(3GdCHOGd deG Yde aj GdMGds - (3YeQ Hf jhSa Hf YeQ Hf Ydj Hf QShd, CHh MaU, eegO GdOjf, Gdedc GdCTQa,J (B696 (3g` s
(3ChdgG (B:s
(3gPG cJGH LeYJ ajg eG hLOJg ef CHOGd GdCOhjI GdeaQOI ai GdWH EPG cGf TF efgG YfO GdMGLI bO jYde ajHOd Yfg eG bGdJ GdMceGA hCdaJg Ydi MQha GdeYLe s
(3BNQgG (B:s
(3bGd UGMH GdbGfhf (B: (3HOG dgG ai GSJaQGZ GdeGFjI hGdHZejI hajg fXQ jHMK Yfg Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3cJHJ GSeGA GdCOhjI HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B6s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (Bf - (3bSe GdcJGH GdKGfi (B- (3U (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdWHs